2015
DOI: 10.2196/resprot.4049
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Web Site Usage of e-Bug: A Hygiene and Antibiotic Awareness Resource for Children

Abstract: Backgrounde-Bug is an educational resource which teaches children and young people about microbes, hygiene, infection, and prudent antibiotic use. The e-Bug resources are available in over 22 different languages and they are used widely across the globe. The resources can be accessed from the e-Bug website.ObjectiveThe objective of this study was to analyze the usage of the e-Bug website in order to understand how users access the website, where and when they access the site, and to review variation in use acr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 13 publications
1
14
0
1
Order By: Relevance
“…Social media campaigns, games and email/text messaging may be a more useful avenue to explore than leaflets 23–25. Educational resources for school-age children developed by the e-Bug project26 have been deployed across Europe27 and downloaded worldwide,28 and a recent feasibility study showed that 72% of those aged 16–18 years who had participated in an e-Bug lesson consented to receive follow-up text messages asking about their antibiotic use (unpublished PHE data). Our survey took place before the launch of PHE’s ‘Keep Antibiotics Working’ campaign which included advertisements on television, radio and social media.…”
Section: Discussionmentioning
confidence: 99%
“…Social media campaigns, games and email/text messaging may be a more useful avenue to explore than leaflets 23–25. Educational resources for school-age children developed by the e-Bug project26 have been deployed across Europe27 and downloaded worldwide,28 and a recent feasibility study showed that 72% of those aged 16–18 years who had participated in an e-Bug lesson consented to receive follow-up text messages asking about their antibiotic use (unpublished PHE data). Our survey took place before the launch of PHE’s ‘Keep Antibiotics Working’ campaign which included advertisements on television, radio and social media.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that the e-Bug website is accessed most during the academic terms especially during the winter term in January and February (Young et al 2015). Future research should explore why there is a peak in e-Bug use during the winter term but this is most likely due to cold and flu season.…”
Section: Comparison With Existing Literaturementioning
confidence: 97%
“…The online activity of users on the e-Bug website has also been evaluated and continues to be monitored (de Quincey et al 2011). Further research has shown that the e-Bug website is frequently used throughout Europe with the majority of visitors being from the United Kingdom (Young et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…3). Google analytics of the e-Bug website reported Chicken Surprise as one of the most popular student games (Young et al, 2015). Outside of the school setting, educational games have been used in food industry as a means of training hygiene skills in workers.…”
Section: Communicating Risk Through Gamesmentioning
confidence: 99%